Sleep and nighttime energy consumption in early childhood: a population‐based cohort study. Issue 6 (7th January 2015) - McDonald, L.; Wardle, J.; Llewellyn, C. H.; Johnson, L.; van Jaarsveld, C. H. M.; Syrad, H.; Fisher, A.
Summary: Background: Shorter sleep is a risk factor for weight gain in young children. Experimental studies show that sleep deprivation is associated with higher nighttime energy intake, but no studies have examined the patterning of energy intake in relation to nighttime sleep duration in young children. Objectives: The objectives of the study were to test the hypothesis that shorter‐sleeping children would show higher nighttime energy intake and to examine whether the additional calories were from drinks, snacks or meals. Methods: Participants were 1278 families from the Gemini twin cohort, using data from one child per family selected at random to avoid clustering effects. Nighttime sleep duration was measured at 16 months of age using the Brief Infant Sleep Questionnaire. Energy intake by time of day and eating episode (meal, snack, drink) were derived from 3‐day diet diaries completed when children were 21 months. Results: Consistent with our hypothesis, shorter‐sleeping children consumed more calories at night only (linear trend P < 0.001), with those sleeping <10 h consuming on average 120 calories (15.2% of daily intake) more at night than those sleeping ≥13 h. The majority of nighttime intake was from milk drinks. Associations remained after adjusting for age, sex, birth weight, gestational age, maternal education, weight and daytime sleep. Conclusions: Shorter‐sleeping, young children consume more calories, predominantly at night, and from milk drinks. Parents should be aware that providing milk drinks at night may contribute to excess intake. This provides a clear target for intervention that may help address associations between sleep and weight observed in later childhood.